Characterization of an Acidic Polysaccharides from Carrot and Its Hepatoprotective Effect on Alcoholic Liver Injury in Mice. Issue 8 (13th July 2021) - Kong, Xiangying; Liang, Wei; Li, Xinyue; Qiu, Meng; Xu, Wenjun; Chen, Hongman
Abstract: The characteristics of acidic polysaccharides extracted from Daucus carota L. var. sativa Hoffm were investigated and its hepatoprotective effects on alcoholic liver injury were determined in the mice model. A carrot polysaccharide (CPS‐I: Carrot polysaccharide‐I) with the molecular weight of 3.40×10 4  kDa was isolated from Daucus carota  L. and purified by diethylaminoethyl‐52 and Sephadex G‐150 column chromatography. The components were analyzed by HPLC, which revealed that CPS‐I consisted of galacturonic acid, rhamnose, xylose, arabinose, fructose, and galactose at a relative ratio of 1 : 3.16 : 1.13 : 5.53 : 3.45 : 7.76. Structural characterization analysis suggested that CPS‐I was mainly composed of →6)‐β‐D‐Galp‐(1→ and →5)‐α‐L‐Araf‐(1→. The hepatoprotective effect of CPS‐I was evaluated by alcoholic liver injury mice model. The results showed that the administration of CPS‐I (300 mg/kg/day) alleviated the alcoholic liver injury in mice by increasing the levels of ADH and ALDH and reducing oxidative stress. CPS‐I ameliorated the pathological changes of liver characterized by lipid accumulation, and reduced the number of lipid droplets. Abstract :